2019
DOI: 10.1111/joor.12870
|View full text |Cite
|
Sign up to set email alerts
|

Tactile trigeminal region acuity in temporomandibular disorders: A reliability and cross‐sectional study

Abstract: Background Two‐point discrimination (2‐PD) is a valuable test for measuring tactile acuity that provides relevant information about cortical reorganisation and somatosensory function. Objectives The main objectives of the present study were to assess intra‐ and interexaminer reliability of the 2‐PD test in the trigeminal region in asymptomatic individuals and only intra‐examiner reliability in patients with temporomandibular disorders (TMD). The secondary objective was to observe the correlations of the 2‐PD t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…For example, in chronic neck [40], low back pain [41] and complex regional pain syndrome [42], activity levels are changed in the somatosensory cortex (S1). In comparison with healthy subjects, TMD patients suffering from myofascial pain have a decreased S1 grey-matter volume as defined by structural MRI, which may be expressed in a reduced sensory function [43], supported by the results obtained at the two-point discrimination test, which indicates a decrease in the discriminative threshold [34]. Tactile acuity depends strictly on the correct functioning of the somatosensory system; thus, the two-point discrimination test has been suggested as a good assessment tool to evaluate S1 area and the somatosensory function [34].…”
Section: Motor and Somatosensory Disturbances In Cofpmentioning
confidence: 75%
See 1 more Smart Citation
“…For example, in chronic neck [40], low back pain [41] and complex regional pain syndrome [42], activity levels are changed in the somatosensory cortex (S1). In comparison with healthy subjects, TMD patients suffering from myofascial pain have a decreased S1 grey-matter volume as defined by structural MRI, which may be expressed in a reduced sensory function [43], supported by the results obtained at the two-point discrimination test, which indicates a decrease in the discriminative threshold [34]. Tactile acuity depends strictly on the correct functioning of the somatosensory system; thus, the two-point discrimination test has been suggested as a good assessment tool to evaluate S1 area and the somatosensory function [34].…”
Section: Motor and Somatosensory Disturbances In Cofpmentioning
confidence: 75%
“…The cortical disinhibition, together with the central sensitization, present in chronic pain, also drives changes in primary sensory areas and leads to perceptual disturbances [33]. It has been demonstrated that COFP presents with altered epicritic sensibility, due to the presence of reduced tactile acuity [34], altered tactile detection threshold [35] and worse laterality discrimination [36]. Furthermore, proprioceptive and non-proprioceptive alterations, which are manifested through body, perceptual distortions [37] and disturbances of internal and external emotions recognition, have been found in these patients [38,39].…”
Section: Dysfunctional Cofpmentioning
confidence: 99%
“…It is also important to note that the TMD may be associated with body (face) disruption, which can be expressed as alexithymia (a lack of emotional expression and emotional recognition), changes in two-point discrimination, and (facial) motor disturbances [ 105 , 106 , 107 ]. This situation may lead to facial dysmorphic disorders (dysfunctional body image, in this case of the subject’s face) [ 108 ] or prosopagnosia (a severe deficit in recognizing familiar people from their face) [ 109 ].…”
Section: Scientific Evidence Of Top-down Interventionsmentioning
confidence: 99%
“…However, while animal studies showed that during central sensitisation nociceptive and wide dynamic range neurons develop tactile sensitivity, and animals acquire a facial mechanical hypersensitivity due to a lowered threshold to mechanical stimuli, 30 it is unknown whether this leads to an increased tactile acuity. To add, tactile acuity is decreased in patients with chronic pain including TMD‐pain, 13,31 and delayed‐onset muscle soreness of the masticatory muscles did not affect OTA 22 . Thus, in spite of the animal studies findings, central sensitisation might not be the main mechanism involved in OTA enhancement.…”
Section: Discussionmentioning
confidence: 86%
“…A recent clinical study demonstrated that tactile acuity in the trigeminal region of patients with temporomandibular disorders (TMD) is impaired 13 . Also, patients with oro‐facial pain complaints frequently report unpleasant sensations associated with somatosensory dysfunction 14 .…”
Section: Introductionmentioning
confidence: 99%